Niobium Pentoxide Samples with Addition of Manganese at Different Concentrations and Calcination Temperatures Applied in the Photocatalytic Degradation of Rhodamine B (2020)
In order to improve the photocatalytic effect of Nb2O5, manganese from 1% to 10% was added by the polymeric precursor’s method. The samples obtained were subjected to different calcination temperatures from 400 to 700 °C. Characterization of the synthesized materials was performed by XRD, IR, Raman and Diffuse Reflectance Spectroscopy (DRS) spectroscopy, FE-SEM, Brunauer–Emmett–Teller (BET) method, Photoluminescence (PL) and Dynamic Light Scattering (DLS). Photocatalytic performance for degradation of Rhodamine B was also evaluated. The Rietveld refined X-Ray Diffraction (XRD) pattern of Nb2O5:Mn 1.0 wt.% (700 °C) sample was similar to that of the un-doped oxide, therefore indicating that Nb was replaced by Mn and, consequently, there are not significant variations in the oxide structure. The Nb2O5:Mn 10.0 wt.% (700 °C) sample has the lowest band gap energy. The specific surface area (SBET) PL value increased as manganese concentration increased. The Nb2O5:Mn 5.0 wt.% (700 °C) sample has an Eg of 3.15 eV and morphological and surface characteristics that made it an appropriate photocatalyst in the Rhodamine B degradation. The novelty of this work relies on the use of a small quantity of Mn ions as dopants leading to Nb2O5:Mn nanostructured particles without using any surfactant or other additives